Influence of oxygen enriched gases during decompression on bubble formation and endothelial function in self-contained underwater breathing apparatus diving: a randomized controlled study - Šegrt Ribičić, Ivana (Croat Med J, 2019)
AIM: To assess the effect of air, gas mixture composed of 50% nitrogen and 50% oxygen (nitrox 50), or gas mixture composed of 1% nitrogen and 99% oxygen (nitrox 99) on bubble formation and vascular/endothelial function during decompression after self-contained underwater breathing apparatus diving. METHODS: This randomized controlled study, conducted in 2014, involved ten divers. Each diver performed three dives in a randomized protocol using three gases: air, nitrox 50, or nitrox 99 during ascent. The dives were performed on three different days limited to 45 m sea water (msw) depth with 20 min bottom time. Nitrogen bubbles formation was assessed by ultrasound detection after dive. Arterial/endothelial function was evaluated by brachial artery flow mediated dilatation (FMD) before and after dive. RESULTS: Nitrox 99 significantly reduced bubble formation after cough compared with air and nitrox 50 (grade 1 vs 3 and vs 3, respectively, P = 0.026). Nitrox 50 significantly decreased post-dive FMD compared with pre-dive FMD (3.62 ± 5.57% vs 12.11 ± 6.82% P = 0.010), while nitrox 99 did not cause any significant change. CONCLUSION: Nitrox 99 reduced bubble formation, did not change post-dive FMD, and decreased total dive duration, indicating that it might better preserve endothelial function compared with air and nitrox 50 dive protocols.